Research on the suitability of production, living and ecological space development in Duolun County, Inner Mongolia - Liu, Dongchang; Aruhan,; Na, Sai (Frontiers in Environmental Science, 2025)
The Production-Living-Ecological Space (PLES) serve as a crucial link for regional sustainable development, making the study of their development suitability of significant importance. This research focuses on Duolun County in Inner Mongolia, utilizing meteorological and soil data from 2000 to 2020. Advanced statistical models, including geographically weighted regression and spatial autocorrelation analysis, were employed to systematically analyze the spatiotemporal evolution characteristics of PLES development suitability and spatial conflicts. The findings reveal that: (1) The suitability of production space, ecological space, and the comprehensive suitability of PLES in the study area exhibit a spatial differentiation pattern with higher values in the southwest and lower values in the northeast. Specifically, the suitability of production space and the average suitability index of living space show a slight upward trend, while the suitability of ecological space and the comprehensive suitability index of PLES display a downward trend. (2) From the perspective of spatial center migration, the suitability centers of production space and living space have shifted towards the southwest, whereas the functional centers of ecological space and the comprehensive suitability centers of PLES have moved towards the northeast. (3) The spatial distribution characteristics indicate that the suitable areas for PLES are mainly concentrated in the central and southern parts of the county, with the ecological space suitable area being the largest. The non-suitable areas are predominantly distributed in the northern part of the county. The study suggests that the incoordination of PLES suitability is the primary contradiction restricting the development of land space in the county, and land use patterns are the key factors affecting the coupling coordination degree of PLES suitability. Based on these findings, it is recommended that county spatial planning should fully consider the suitability evaluation results and formulate differentiated development strategies according to local conditions to achieve regional sustainable development goals.